Os odontoideum: a rare cause of syncope - Buntting, Christopher Shane (BMJ Case Rep, 2019)
Syncopal events are a concerning presentation and timely evaluation is warranted. Common aetiologies include cardiac and neurological pathology such as arrhythmias, vertebrobasilar arterial disease and vasovagal syncope. We describe the case of a 65-year-old man who presented to our emergency department with symptoms of vertigo and syncope. He was investigated extensively for both cardiac and neurological causes of his symptoms which returned negative results. An outpatient CT scan demonstrated the presence of Os odontoideum and dynamic instability of the atlantoaxial junction, with presumed dynamic obstruction of the vertebral arterial system. This was successfully managed with a posterior atlantoaxial lateral mass fusion with resolution of syncopal symptoms.